Comparative study of prophylactic dexamethasone versus placebo for reducing post-operative sore throat after tracheal intubation: a prospective, randomised, double blinded clinical study - George, Neethu; Mathew, Sumesh (International Journal of Research in Medical Sciences, 2020)
Background: Tracheal intubation for elective surgical procedures can result in pathological changes, trauma and nerve damage which may account for postoperative sore throat, hoarseness and cough. Dexamethasone is a very potent long acting glucocorticoid with analgesic, anti-inflammatory and antiemetic effects which helps to reduce post-operative sore throat. Methods: A prospective double blinded randomized study was conducted involving 80 patients, dividing them into 2 groups. Group D received dexamethasone 0.1 mg/kg and group S received an equivalent volume of normal saline (placebo) intravenously before induction. Intubation was performed by an experienced anesthesiologist. Anesthesia induction and maintenance dosage were standardized for all patients. The incidence and severity of sore throat, hoarseness and cough were recorded at 1, 6 and 24 hours postoperatively by using four-point scale. Results: The overall incidence of sore throat and hoarseness was significantly reduced in dexamethasone group compared to placebo (normal saline) group. Incidence and severity of sore throat and hoarseness were assessed at 1 hour, 6 hours and 24 hours interval and found out that they were reduced in dexamethasone group compared to placebo group which was statistically significant at all intervals. But incidence and severity of cough reduced significantly only in the first hour. It was comparable at 6 and 24 hours between the groups. Conclusions: Dexamethasone was effective in reducing the incidence and severity of sore throat and hoarseness at 1, 6 and 24 hours. Incidence of postoperative cough was reduced significantly at 1 hour in the dexamethasone group.